Morphostructural characterization of female and young male of naturalized Sul-mato-grossenses "Pantaneiros" sheep - Oliveira, Daniele Portela de; Oliveira, Carlos Antonio Lopes de; Martins, Elias Nunes; Vargas Junior, Fernando Miranda; Barbosa-Ferreira, Marcos; Seno, Leonardo Oliveira; Oliveira, Junior Cezar Kawakita de; Sasa, Aya (Semina: Ciências Agrárias, 2014)
Morphometric measurements are important to evaluate the variability, determine the racial standard and the existence of sexual dimorphism in genetic group. With this objective, were measured 20 morphometric measurements and one measurements of weight for 338 animals of the genetic group of Sul-mato-grossenses naturalized sheep belonging to Manoel de Barros Foundation and breeding at Centro Tecnologico de Ovinos from Anhanguera-Uniderp University and Federal University of the Grande Dourados. The statistical analyses were realized through software SAS. The females and young males showed short variation for morphometric measured of head and limbs region. However, higher variation was observed in the morphometric measurements taken from torso region, indicate that this region could be inserted in breeding programs like a selection criterion. The Pearson correlation coefficients between the morphostructural characteristics of females and young males, appears to have certain harmony degree in the morphostructural model. The females are characterized by animals with relatively large head, torso with proportional features and good angulations. The gender did not influence characteristics of the head region and body weight in the young animals. However, the characteristics of other regions, such as thoracic perimeter and posterior width of rump measured in the head region, and the perimeter of carpal and metacarpal in the limbs were influenced by gender in young animals.